2015
DOI: 10.1039/c5ta02114f
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of hydrogen evolution under visible light over Zn1−2x(CuGa)xGa2S4photocatalysts by synthesis utilizing a polymerizable complex method

Abstract: Single phase Zn 1À2x (CuGa) x Ga 2 S 4 was successfully synthesized by a two-step route: synthesis of an oxide precursor by a polymerizable complex (PC) method followed by sulfurization under a H 2 S-Ar flow. The samples thus obtained were porous aggregates consisting of fine crystals with 50 nm size. Among the examined compositions, Zn 0.4 (CuGa) 0.3 Ga 2 S 4 (x ¼ 0.3) showed the highest activity for H 2 evolution from an aqueous solution containing S 2À and SO 3 2À as electron donors under visible light irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…The small variation of a VBM potential at lower x value than 0.5 is because of the relatively large bandgap bowing of (ZnSe) x (CIGS) 1-x material system. The results for both the lattice parameter and the VBM are similar to those reported for (ZnSe) x (CuInSe 2 ) 1-x by Li et al, and for (ZnS) x (CuGaS 2 ) 1-x by Quintans et al [36,37] It should be noted that the Mott-schottky plots revealed that the flat-band potential of (ZnSe) 0.89 (CIGS) 0.11 is about 0.2 V higher than that of CIGS indicating the about 0.2 V deeper VBM potential of (ZnSe) 0.89 (CIGS) 0.11 than that of CIGS. (see Figure S12 in the Supporting Information) The variation of the VBM potential between (ZnSe) 0.89 (CIGS) 0.11 and CIGS estimated by Mott-Schottky plots are consistent with PESA results.…”
supporting
confidence: 88%
“…The small variation of a VBM potential at lower x value than 0.5 is because of the relatively large bandgap bowing of (ZnSe) x (CIGS) 1-x material system. The results for both the lattice parameter and the VBM are similar to those reported for (ZnSe) x (CuInSe 2 ) 1-x by Li et al, and for (ZnS) x (CuGaS 2 ) 1-x by Quintans et al [36,37] It should be noted that the Mott-schottky plots revealed that the flat-band potential of (ZnSe) 0.89 (CIGS) 0.11 is about 0.2 V higher than that of CIGS indicating the about 0.2 V deeper VBM potential of (ZnSe) 0.89 (CIGS) 0.11 than that of CIGS. (see Figure S12 in the Supporting Information) The variation of the VBM potential between (ZnSe) 0.89 (CIGS) 0.11 and CIGS estimated by Mott-Schottky plots are consistent with PESA results.…”
supporting
confidence: 88%
“…CuGaS 2 has a direct band gap of 2.4 eV, which makes it less interesting for use in solar cells than CuInS 2 . However, since the wider band gap of CuGaS 2 is due to its CBM located at a more negative potential than that of CuInS 2 (Figure ), it can still serve as a photocathode for water reduction. It may also be used for other solar fuel production reactions that require more negative potentials than hydrogen production.…”
Section: Electrochemical Synthesis Of Photocathodesmentioning
confidence: 99%
“…For acquiring solar hydrogen, water splitting has been actively investigated using both photoelectrochemical and photocatalytic approaches. [1][2][3][4][5][6][7][8][9][10][11] Since the discovery of photoelectrochemical water splitting by Honda and Fujishima, 12 TiO 2 has been recognised as one of the most efficient photoanodes for the evolution of O 2 from water. Various types of structures with TiO 2 have been fabricated based on novel approaches.…”
mentioning
confidence: 99%